PEMBUATAN CRACKERS DENGAN PENAMBAHAN TEPUNG IKAN LEMURU (SARDINELLA LONGICEPS) - Artama, Trimurti (LPPM Universitas Terbuka, 2003)
This research was done in order to diversify and to increase nutrition value of food product especially to enrich nutrition of fisheries product. Fish flour was made from Sardinella longiceps and wheat flour was used as materials to make crackers. The fish and wheat flour in the ratio of (0:100; 10:90; 20:80 and 30:70) were tested to get the best quality of crackers. Sensory quality, proximate analysis and texture test were applied in all products. The protein quality (chemical score) and calcium contents of the best crackers were 89.60 (limited amino acid : methionine) and 550 mg/100 g, respectively.The result of this research showed that the 20% fish flour-added crackers product had the highest rate of sensory quality (color, taste, smell, performance, and texture). It was accepted well by the panelists, and it also increased the protein quality and the calsium content.